Integration of acssess control in information systems - Thion, Romuald (Informatica (Ljubljana), 2006)
Pervasive computing and proliferation of smart gadgets lead organizations to open their inofrmation systems, especially by extensive use of mobile technology: information systems must be available any-time, any-where, on any media. This cannot be done reasonably without thorough access control policies. Such access control must be able to deal with user profile, time and even with more complex contexts including geographical position. This paper shows that it is possible to take into account confidentiality constraints straight into logical data model in a homogeneous way, for various aspects treated independently (user profile, time, geographical positin, etc.) We propose a language called RAPOOL which allows the expression of authorizations at the class level. We first present the syntactical aspects, then the semantics of the language, based on the object-oriented paradigm.
Keywords: informacijski sistemi; mobilne telekomunikacije; objektno orientirano programiranje; security; varnost